ANALYSIS OF SHANNON CAPACITY FOR SC AND MRC DIVERSITY SYSTEMS IN α-κ-μ FADING CHANNEL - Savić, Milan; Smilić, Marko; Jakšić, Branimir (Bulletin of Natural Sciences Research, 2018)
In this paper, the analysis of Shannon capacity for selection combining (SC) and maximal ratio combining (MRC) diversity systems in the generalized α-κ-μ fading channel is presented. Closed-form expressions for probability density function (PDF) at the output of SC and MRC diversity systems are given. Also, closed-form expressions for Shannon capacity for cases of SC diversity with independent and identically distributed branches, MRC diversity with independent and identically distributed branches and for case of no diversity are derived. The obtained results are numerically calculated and graphically presented for different combinations of fading parameters α, κ and μ.